Emerging nanotechnology role in the development of innovative solutions against COVID-19 pandemic. (8th September 2021) - Bhutta, Zeeshan Ahmad; Kanwal, Ayesha; Ali, Moazam; Kulyar, Muhammad Fakhar-e-Alam; Yao, Wangyuan; Shoaib, Muhammad; Ashar, Ambreen; Mahfooz, Ashar; Ijaz, Misbah; Ijaz, Nabeel; Asif, Muhammad; Nawaz, Shah; et al.
Abstract: The COVID-19 outbreak is creating severe impressions on all facets of the global community. Despite strong measures worldwide to try and re-achieve normalcy, the ability of SARS-CoV-2 to survive sturdy ecological settings may contribute to its rapid spread. Scientists from different aspects of life are working together to develop effective treatment strategies against SARS-CoV-2. Apart from using clinical devices for patient recovery, the key focus is on developing antiviral drugs and vaccines. Given the physical size of the SARS-CoV-2 pathogen and with the vaccine delivery platform currently undergoing clinical trials, the link between nanotechnology is clear, and previous antiviral research using nanomaterials confirms this link. Nanotechnology based products can effectively suppress various pathogens, including viruses, regardless of drug resistance, biological structure, or physiology. Thus, nanotechnology is opening up new dimensions for developing new strategies for diagnosing, preventing, treating COVID-19 and other viral ailments. This article describes the application of nanotechnology against the COVID-19 virus in terms of therapeutic purposes and vaccine development through the invention of nanomaterial based substances such as sanitizers (handwashing agents and surface disinfectants), masks and gowns, amongst other personal protective equipment, diagnostic tools, and nanocarrier systems, as well as the drawbacks and challenges of nanotechnology that need to be addressed.